Intrusion detection model based on improved transformer - Gavrylenko, Svitlana; Poltoratskyi, Vadym; Nechyporenko, Alina (Національний технічний університет "Харківський політехнічний інститут", 2024)
The object of the study is the process of identifying the state of a computer network. The subject of the study are the methods of identifying the state of computer networks. The purpose of the paper is to improve the efficacy of intrusion detection in computer networks by developing a method based on transformer models. The results obtained. The work analyzes traditional machine learning algorithms, deep learning methods and considers the advantages of using transformer models. A method for detecting intrusions in computer networks is proposed. This method differs from known approaches by utilizing the Vision Transformer for Small-size Datasets (ViTSD) deep learning algorithm. The method incorporates procedures to reduce the correlation of input data and transform data into a specific format required for model operations. The developed methods are implemented using Python and the GOOGLE COLAB cloud service with Jupyter Notebook. Conclusions. Experiments confirmed the efficiency of the proposed method. The use of the developed method based on the ViTSD algorithm and the data preprocessing procedure increases the model's accuracy to 98.7%. This makes it possible to recommend it for practical use, in order to improve the accuracy of identifying the state of a computer system.

Об'єктом дослідження є процес ідентифікації стану комп'ютерної мережі. Предметом дослідження є методи ідентифікації стану комп'ютерних мереж. Метою статті є підвищення якості виявлення вторгнень у комп'ютерні мережі шляхом розробки методу на основі моделей-трансформерів. Отримані результати. У роботі проаналізовано традиційні алгоритми машинного навчання та методи глибокого навчання, розглянуто переваги використання моделейтрансформерів. Запропоновано метод виявлення вторгнень в комп'ютерні мережі, який відрізняється від відомих використанням алгоритму глибокого навчання Vision Transformer for Small-size Datasets (ViTSD), містить процедури зменшення кореляції вихідних даних та перетворення табличних вихідних даних у спеціальний формат, необхідний для роботи моделей. Досліджені методи реалізовані програмно з використанням хмарного сервісу GOOGLE COLAB на основі Jupyter Notebook. Висновки. Проведені експерименти підтвердили працездатність запропонованого методу. Отримано, що використання розробленого методу на основі алгоритму ViTSD та процедури попередньої обробки даних надає можливість підвищити точність моделі до 98,7%. Це надає можливість рекомендувати його для практичного використання з метою підвищення точності ідентифікації стану комп’ютерної системи.
Модель виявлення вторгнень на основі покращеного трансформера
Keywords: data preprocessing; machine learning; neural networks; RNN; SVM; KNN; transformer models; vision transformer; попередня обробка даних; машинне навчання; нейронні мережі; моделі-трансформери